Attentional bias for alcohol cues in visual search—Increased engagement, difficulty to disengage or both? - Heitmann, Janika (PLoS One, 2020)
Cognitive models emphasise the importance of attentional bias in addiction. However, many attentional bias tasks have been criticised for questionable psychometric properties and inability to differentiate between engagement and disengagement processes. This study therefore examined the suitability of two alternative tasks for assessing attentional bias within the context of alcohol use. Participants were undergraduate students (N = 169) who completed the Visual Search Task and Odd-One-Out Task, the latter of which is designed to differentiate between engagement and disengagement processes of attention, at baseline and one week later. Participants also completed baseline measures of alcohol consumption, craving, and alcohol use problems. Internal consistency was adequate for the Visual Search Task index, and weak for the Odd-One-Out Task indices. Test-retest reliability was weak for both tasks. The Visual Search Task index and the disengagement (but not the engagement) index of the Odd-One-Out Task showed a positive association with alcohol consumption. This study was restricted to a non-clinical student sample. The relatively high error rate of the Odd-One-Out Task might have reduced its sensitivity as an index of attentional bias. Both tasks showed some merit as attentional bias measures, and results suggested that attentional disengagement might be particularly related to alcohol use. However, the reliability of the current measures was inadequate. One potential explanation for the low reliability is that non-clinical samples may have weak and unstable attentional biases to alcohol. Future efforts should be made to improve the psychometric qualities of both tasks and to administer them in a clinical sample.